Peranan Sekuen Stir Pada Pemeriksaan MRI Shoulder Dengan Klinis Supraspinatus Injury Di Instalasi Radiologi Rumah Sakit Umum Pusat Persahabatan Jakarta Timur - Zul Fikra; I Made Lana Prasetya; Hendra Setiawan (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2023)
Magnetic Resonance Imaging (MRI) is a diagnostic examination modality in medical science using a magnetic field without using X-rays. MRI has the advantage of being able to create images and showing clearer and more sensitive anatomical differences in soft tissues in the body such as the extremities, brain, bone marrow and musculoskeletal to establish a clinical diagnosis, one of which is Supraspinatus Injury to the Shoulder. Supraspinatus is a tear or rupture of the tendon of the supraspinatus muscle. The supraspinatus is part of the shoulder rotator cuff. Most of the time, it is accompanied by another rotator cuff muscle tear. This can occur due to trauma or repeated microtrauma and appears as a partial or full thickness tear. The rotator cuff is a fibrous connective tissue that surrounds the top of the humerus bone and functions to maintain the stability of the glenohumeral joint by pulling the humerus towards the scapula. The research method used is qualitative descriptive research with an observational approach. Data collection was carried out from 08 August 2023 to 07 September 2023 using the Mri Philips Achieva 1.5 Hestia aircraft. The patient sample used in this study was a patient with shoulder complaints. Data collection was carried out through observation, interviews and documentation. Shoulder MRI examination in Supraspinatus Injury Cases using a Philips 1.5 Hestia MRI aircraft has an examination procedure with a sequential design Survey, STIR_TSE_Tra, T1W_TSE_Tra, T1W_TSE_TRA_FS, STIR_TSE_Cor, COR_T2W_FFE, STIR_TSE_Sag, T1W_TSE_Cor, PDW_TSE_Sag